2020
DOI: 10.1016/j.ijid.2020.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Patients of COVID-19 may benefit from sustained Lopinavir-combined regimen and the increase of Eosinophil may predict the outcome of COVID-19 progression

Abstract: Highlights Asymptomatic 2019-coronavirus disease patient with normal radiography throughout appeared in this study.  Lopinavir has an positive effect on 2019-coronavirus disease patients.  Eosinophil counts presented potentiality as predictor on the progression of 2019-coronavirus disease. J o u r n a l P r e -p r o o f Abstract Objectives: To explore the epidemiological information, clinical characteristics, therapeutic outcomes and temporal progression of laboratory findings in 2019-coronavirus disease (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
329
2
23

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 330 publications
(381 citation statements)
references
References 9 publications
19
329
2
23
Order By: Relevance
“…Interestingly, almost all patients (134, 95.0%) showed eosinophil count less than 0.10 × 10 9 /L in the early stages of the disease, and especially in severe patients, the eosinophil count was generally very low and returned to normal levels upon convalescence. This may be associated with a mechanism of stress response in the condition of acute lung injury caused by SARS-CoV-2, which inhibits the release of eosinophil in the bone marrow through glucocorticoid secretion [20]. As the disease recovers, the eosinophil gradually returns to normal levels, which means that decreasing and increasing eosinophil may be the signs of disease progression and recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, almost all patients (134, 95.0%) showed eosinophil count less than 0.10 × 10 9 /L in the early stages of the disease, and especially in severe patients, the eosinophil count was generally very low and returned to normal levels upon convalescence. This may be associated with a mechanism of stress response in the condition of acute lung injury caused by SARS-CoV-2, which inhibits the release of eosinophil in the bone marrow through glucocorticoid secretion [20]. As the disease recovers, the eosinophil gradually returns to normal levels, which means that decreasing and increasing eosinophil may be the signs of disease progression and recovery.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 2,355,853 recorded cases were registered, with 164,656 fatalities as of the 20 April 2020 [13]. On 29 January 2020, Li et al's case study reported in the New Britain Journal of Medicine summarizes the 425 first documented cases in Wuhan [3,14].…”
Section: Coronavirus Familymentioning
confidence: 99%
“…Lopinavir (LPV) is a HIV type 1 aspartate protease inhibitor while ritonavir (RTV) is usually combined to it to increase the plasma half-life of LPV by inhibiting CYP450 enzyme [14]. Since the outbreak, several clinical trials have been investigated on the potentials of this combination (LPV/RTV) on SARS-CoV-2 patients outcomes.…”
Section: Antiviral Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eosinophils have also been reported to be decreased in previous studies 17,18 . Increasing eosinophil count may even be a predictor of improvement in patients with SARS-Cov-2 infection 19 . A low proportion of basophils has also been reported in severe cases 12 but no previous study has reported low basophil cell count as a marker of SARS-Cov-2 infection.…”
Section: Discussionmentioning
confidence: 99%